1997
DOI: 10.1002/jlb.62.4.469
|View full text |Cite
|
Sign up to set email alerts
|

Humanized mAb H22 binds the human high affinity Fc receptor for IgG (FcγRI), blocks phagocytosis, and modulates receptor expression

Abstract: Abstract:About

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 1 publication
3
23
0
Order By: Relevance
“…31 and data not shown), which do not bind antiFc␥RI constructs. This is in accordance with modulation studies by Wallace et al (24), which demonstrated the specificity of H22 for Fc␥RI. Furthermore, Fc␥RI modulation in our studies was not blocked by Abs to irrelevant cell surface receptors, Fc␥RII or CD11b (data not shown), suggesting that those two molecules did not take part in anti-Fc␥RI-mediated modulation of Fc␥RI.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…31 and data not shown), which do not bind antiFc␥RI constructs. This is in accordance with modulation studies by Wallace et al (24), which demonstrated the specificity of H22 for Fc␥RI. Furthermore, Fc␥RI modulation in our studies was not blocked by Abs to irrelevant cell surface receptors, Fc␥RII or CD11b (data not shown), suggesting that those two molecules did not take part in anti-Fc␥RI-mediated modulation of Fc␥RI.…”
Section: Discussionsupporting
confidence: 93%
“…We also explored the contribution of the relative level of receptor expression and the presence of ligand on modulation. Our findings suggest that trivalent anti-Fc␥RI constructs modulate Fc␥RI in the absence of IgG in a concentration-dependent manner similar to the modulation of monocyte Fc␥RI reported by Wallace et al (24), although the kinetics of modulation are more rapid on 10.6 cells. However, the presence of IgG leads to greater modulation at higher concentrations of modulator and permits the internalization of non-crosslinked anti-Fc␥RI constructs.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…PBLs were depleted of granulocytes and RBCs by Ficoll density centrifugation. Monocyte depletion, when done, was accomplished by cold aggregation performed by Joseph D. Tario of the Roswell Park Flow Cytometry Facility (15).…”
Section: Patient Samplesmentioning
confidence: 99%